Abrupt SiGe and Si Profile Fabrication by Introducing Carbon Delta Layer. (1st January 2017) - Yamamoto, Yuji; Zaumseil, Peter; Schubert, Markus Andreas; Hesse, Anne; Murota, Junichi; Tillack, Bernd
Abstract : High quality and steep Si/Si0.5 Ge0.5 /Si profile is fabricated by introducing a C delta layer at the interface using reduced pressure chemical vapor deposition system. The Si0.5 Ge0.5 and Si layers are deposited by H2 -SiH4 -GeH4 at 500°C and H2 -Si2 H6 at 500°C to 575°C, respectively. By introducing a C delta layer at the surface, roughening of the Si0.5 Ge0.5 surface is maintained at 575°C due to suppressed surface migration of Si and Ge as well as defect injection into the Si0.5 Ge0.5 layer resulting in high crystallinity Si cap layer growth. Adsorbed CH3 species at the surface are preventing the epitaxial Si cap layer growth at 500°C, but it is possible to deposit high quality epitaxial Si at higher temperature because of hydrogen-desorption from adsorbed CH3 . Interdiffusion of Si and Ge at the interface is observed at 525°C in the case of sample without C delta layers, but the interdiffusion is suppressed even at 575°C by introducing C delta layers.